Analyzing VOA’s YouTube videos for effective idiom learning in ELT: A content-based approach - Lavinia Putri, Avril; Seinsiani, Izzati Gemi (ELT Forum: Journal of English Language Teaching, 2025)
Idiom mastery is a crucial component of English language learning, particularly for enhancing communicative competence and cross-cultural understanding among EFL learners. Despite its importance, idiom learning often faces challenges due to the nonliteral and culturally embedded nature of idioms, as well as insufficient exposure and pedagogical focus in traditional classrooms. This study addresses these gaps by analyzing the types of idioms and their multimodal presentation in VOA's English in a Minute video series, a digital platform designed to teach idioms through short, engaging videos. Employing a qualitative content analysis approach, the study examined ten videos to classify idioms based on Abel's (2003) transparency typology (transparent, semi-transparent, opaque) and to evaluate the multimodal strategies used to support comprehension. The findings revealed that semi-transparent idioms dominated the series (50%), followed by opaque (30%) and transparent idioms (20%), indicating a strategic balance between cognitive challenge and accessibility. The videos consistently employed literal visuals, contextual dialogues, explicit narration, and textual reinforcement to clarify idiomatic meanings, aligning with Dual Coding Theory (Paivio, 1986) and principles of content-based instruction (Brinton et al., 2003). While the series effectively aids comprehension through its structured and engaging format, its brevity and limited cultural depth suggest the need for supplementary instructional support. The study highlights the potential of multimodal digital tools in idiom learning and recommends their integration into broader pedagogical frameworks to enhance both receptive and productive language skills.